2D Metal Oxyhalide‐Derived Catalysts for Efficient CO2 Electroreduction. Issue 38 (8th August 2018) - García de Arquer, F. Pelayo; Bushuyev, Oleksandr S.; De Luna, Phil; Dinh, Cao‐Thang; Seifitokaldani, Ali; Saidaminov, Makhsud I.; Tan, Chih‐Shan; Quan, Li Na; Proppe, Andrew; Kibria, Md. Golam; Kelley, Shana O.; Sinton, David; et al.
Abstract: Electrochemical reduction of CO2 is a compelling route to store renewable electricity in the form of carbon‐based fuels. Efficient electrochemical reduction of CO2 requires catalysts that combine high activity, high selectivity, and low overpotential. Extensive surface reconstruction of metal catalysts under high productivity operating conditions (high current densities, reducing potentials, and variable pH) renders the realization of tailored catalysts that maximize the exposure of the most favorable facets, the number of active sites, and the oxidation state all the more challenging. Earth‐abundant transition metals such as tin, bismuth, and lead have been proven stable and product‐specific, but exhibit limited partial current densities. Here, a strategy that employs bismuth oxyhalides as a template from which 2D bismuth‐based catalysts are derived is reported. The BiOBr‐templated catalyst exhibits a preferential exposure of highly active Bi ( 1 1 ¯ 0 ) facets. Thereby, the CO2 reduction reaction selectivity is increased to over 90% Faradaic efficiency and simultaneously stable current densities of up to 200 mA cm −2 are achieved—more than a twofold increase in the production of the energy‐storage liquid formic acid compared to previous best Bi catalysts. Abstract : A 2D bismuth oxyhalide‐templated catalyst for CO2 electroreduction exhibits an in operando preferential facet exposure, which enables sustaining near‐unity selectivity to formate production even at high current densities up to 200 mA cm −2 .